2011
DOI: 10.1016/j.theriogenology.2011.02.019
|View full text |Cite
|
Sign up to set email alerts
|

Timing of insemination and fertility in dairy and beef cattle receiving timed artificial insemination using sex-sorted sperm

Abstract: The objective was to evaluate the effects of timing of insemination and type of semen in cattle subjected to timed artificial insemination (TAI). In Experiment 1, 420 cyclic Jersey heifers were bred at either 54 or 60 h after P4-device removal, using either sex-sorted (2.1 × 10(6) sperm/straw) or non-sorted sperm (20 × 10(6) sperm/straw) from three sires (2 × 2 factorial design). There was an interaction (P = 0.06) between time of AI and type of semen on pregnancy per AI (P/AI, at 30 to 42 d after TAI); it was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
68
2
15

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(92 citation statements)
references
References 35 publications
7
68
2
15
Order By: Relevance
“…Furthermore, the conception rates for sexed semen were low even for crossbred animals, corroborating the results of other studies with other breeds, including beef cattle, which had low conception rates for insemination with sexed semen (Sales et al, 2011;Sá Filho et al, 2013). The conception rate for sexed semen insemination is between 60% and 90% lower than that observed for conventional semen (Dejarnette et al, 2009;Schenk et al, 2009;Dejarnette et al, 2010;Healy et al, 2013;) and the results of this study are within this range (61.1% -76.4%).…”
Section: Additionally Bombadelli Et Al (2016) Inseminated Lactatingsupporting
confidence: 86%
See 3 more Smart Citations
“…Furthermore, the conception rates for sexed semen were low even for crossbred animals, corroborating the results of other studies with other breeds, including beef cattle, which had low conception rates for insemination with sexed semen (Sales et al, 2011;Sá Filho et al, 2013). The conception rate for sexed semen insemination is between 60% and 90% lower than that observed for conventional semen (Dejarnette et al, 2009;Schenk et al, 2009;Dejarnette et al, 2010;Healy et al, 2013;) and the results of this study are within this range (61.1% -76.4%).…”
Section: Additionally Bombadelli Et Al (2016) Inseminated Lactatingsupporting
confidence: 86%
“…Several authors also observed a statistical difference when comparing sexed and conventional semen, for both estrus detection (Bodmer et al, 2005;Anderson et al, 2006;Sá Filho et al, 2013) and fixed-time artificial insemination (FTAI) (Sales et al, 2011;Mallory et al, 2013;Sá Filho et al, 2013). However, the use of sexed semen is recommended to reach best results after estrus detection (Mallory et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, BCS, AI technician, farm, breeding groups, and sire/semen quality are other factors affecting timed-AI outcomes (PERRY et al, 2007;SÁ FILHO et al, 2009;SALES et al, 2011;CELEGHINI et al, 2017). The absence of these effects (BCS, AI technician, and breeding groups) on CR in the present study may be due to the fact that breeding groups were well distributed across the timed-AI variables, all animals were cows in the same category (suckled multiparous Brangus cows), only two skilled AI technicians inseminated cows, and all animals presented small variation in BCS range (2.25 to 3.00).…”
Section: Resultsmentioning
confidence: 99%